Investigation of Beyler dam lake water quality in terms of some physical and chemical parameters - Abdelali̇, Khalifa Moftah; Taştan, Yiğit; Sönmez, Adem Yavuz (Marine Science and Technology Bulletin, 2018)
This study was carried out for a period of 12 months from September 2016 to August 2017 at 4 stations determined in Beyler Dam Lake in Kastamonu, Turkey. In this study, some parameters such as temperature, pH, conductivity, dissolved oxygen, ammonium, nitrate, nitrite, phosphate, chemical oxygen demand (COD), biological oxygen demand (BOD) were investigated. Temperature, pH, conductivity, turbidity and the amount of dissolved oxygen of the water samples were measured by multi parameter measurement device in the field during sampling. Chemical parameters such as ammonium, nitrate, nitrite, phosphate, BOD and COD were determined by spectrophotometric methods in laboratory conditions. Study indicates such results as; the temperature was between 0.70 and 23.50 ºC and the mean temperature was 11°C, pH was between 7.46 and 9.50 and average pH was 8.34, amount of dissolved oxygen varied from 7.48 to 12.16 mg/l and the average dissolved oxygen amount was 9.73 mg/l, conductivity was between 102.50 and 240 µS cm-1 and the average conductivity was 157.68 µS cm-1, turbidity changed from 1.23 to 5.57 FNU/NTU and the average turbidity was 3.0 FNU/NTU, nitrate varied from 0.003 to 1.0 mg/l and the average nitrate was 0.35 mg/l, nitrite was between 0.001 and 0.007 mg/l and the average nitrite was 0.003 mg/l, ammonium changed from 0.009 and 0.130 mg/l and the average ammonium was 0.052 mg/l, phosphate was between 0.24 and 5.21 mg/l and the average phosphate was 2.541 mg/l, COD which is an important water quality parameters, was detected as the lowest 0.04 mg/l and the highest 28.1 mg/l and the average was found 9.45 mg/l, BOD was detected between 2.50 and 6.0 mg/l and the average BOD was calculated 4.17 mg/l. The results of the study revealed that there is no significant difference between the measured parameters according to the Surface Water Quality Regulation (SWQR) in Turkey. Although Beyler Dam Lake was evaluated as Class I for most parameter values, in total it can be classiﬁed as Class II according to water quality classification.
Keywords: Hidrobiyoloji; beyler dam lake; Naval Science; Beyler Dam Lake; Water quality; Physicochemical parameters; Kastamonu; Turkey; kastamonu; V; physicochemical parameters; Naval architecture. Shipbuilding. Marine engineering; SH1-691; VM1-989; water quality; Aquaculture. Fisheries. Angling; turkey; Hydrobiology; 6. Clean water; 14. Life underwater